Antiviral Efficacy of Selected Natural Phytochemicals against SARS-CoV-2 Spike Glycoprotein Using Structure-Based Drug Designing - Bandar Hamad Aloufi (Molecules, 2022)
SARS-CoV-2 is a highly virulent coronavirus that first surfaced in late 2019 and has since created a pandemic of the acute respiratory sickness known as “coronavirus disease 2019” (COVID-19), posing a threat to human health and public safety. S-RBD is a coronaviral protein that is essential for a coronavirus (CoV) to bind and penetrate into host cells. As a result, it has become a popular pharmacological target. The goal of this study was to find potential candidates for anti-coronavirus disease 2019 (COVID-19) drugs by targeting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) S-RBD with novel bioactive compounds and molecular interaction studies of 15,000 phytochemicals belonging to different flavonoid subgroups. A spike protein crystal structure attached to the ACE2 structure was obtained from the PDB database. A library of 15,000 phytochemicals was made by collecting compounds from different databases, such as the Zinc-database, PubChem-database, and MPD3-database. This library was docked against a receptor binding domain of a spike glycoprotein through the Molecular Operating Environment (MOE). The top drug candidates Phylloflavan, Milk thistle, Ilexin B and Isosilybin B, after virtual screening, were selected on the basis of the least binding score. Phylloflavan ranked as the top compound because of its least binding affinity score of −14.09 kcal/mol. In silico studies showed that all those compounds showed good activity and could be used as an immunological response with no bioavailability issues. Absorption, distribution, metabolism, excretion and a toxicological analysis were conducted through SwissADME. Stability and effectiveness of the docked complexes were elucidated by performing the 100 ns molecular dynamic simulation through the Desmond package.